An empirically-based scenario for the evolution of cultural transmission in the human lineage during the last 3.3 million years - Ivan Colagè; Francesco d’Errico (PLoS ONE, 2025)
Humans accumulate an ever-growing body of knowledge that far exceeds the capacity of any single individual or generation. Social learning and transmission are essential for this process. However, how cultural transmission strategies evolved in our lineage remains unclear. Here we assess the transmission strategies needed to ensure the perpetuation across generations of 103 cultural traits that emerged in the Paleolithic. Our study provides a novel approach to assessing the transmission behaviors implicated in Paleolithic cultural traits and the evolution of cultural transmission over the last 3.3 million years. The results identify trends in the evolution of cultural transmission and reveal a coevolutionary dynamic between the emergence of novel cultural traits and the complexification of transmission strategies. While effective means of overt explanation, perhaps associating gesture and verbal expression, were already present at least 600,000 years ago, the period between 200,000 and 100,000 years ago appears as a crucial tipping point for the emergence of modern language.